The Prohormone Proinsulin as a Neuroprotective Factor: Past History and Future Prospects - de Pablo, Flora; Hernández-Sánchez, Catalina; de la Rosa, Enrique J. (Frontiers in Molecular Neuroscience, 2018)
Proinsulin was first identified as the primary translation product of the insulin gene in Donald Steiner’s laboratory in 1967, and was the first prohormone to be isolated and sequenced. While its role as an insulin precursor has been extensively studied in the field of endocrinology, the bioactivity of the proinsulin molecule itself has received much less attention. Insulin binds isoforms A and B of the insulin receptor (IR) with high affinity. Proinsulin, in contrast, binds with high affinity only to IR-A, which is present in the nervous system, among other tissues, and elicits antiapoptotic and neuroprotective effects in the developing and postnatal nervous system. Proinsulin specifically exerts neuroprotection in the degenerating retina in mouse and rat models of retinitis pigmentosa, delaying photoreceptor and vision loss after local administration in the eye or systemic (intramuscular) administration of an adeno-associated viral (AAV) vector that induces constitutive proinsulin release. AAV-mediated proinsulin expression also decreases the expression of neuroinflammation markers in the hippocampus and sustains cognitive performance in a mouse model of precocious brain senescence. We have therefore proposed that proinsulin should be considered a functionally distinct member of the insulin superfamily. Here we briefly review the legacy of Steiner’s research, the neural expression of proinsulin, and the tissue expression patterns and functional characteristics of IR-A. We discuss the neuroprotective activity of proinsulin and its potential as a therapeutic tool in neurodegenerative conditions of the central nervous system, particularly in retinal dystrophies